Empowering Rural Women Through Handicraft Training: A Case Study on Bridal Gift Making - Iis Makhisoh; Mas’ud; M. Ifan Fahmi (Al-Qalam Institute, 2024)
This study focuses on the economic empowerment of rural women through specialized training in bridal gift (hantaran) crafting in Pacarpeluk Village. The primary objective is to explore how such training can enhance the economic welfare and independence of housewives, who have traditionally been limited in their economic roles. A qualitative research method with a case study approach was employed to gain in-depth insights into the experiences of the participants. Data collection techniques included in-depth interviews, participatory observation, and documentation. The findings reveal that the training significantly increased the participants' technical skills, self-confidence, and economic independence. Participants reported a notable rise in their income and an improved ability to contribute to their household finances. The implications of this study suggest that integrating technical skills training with community support can lead to sustainable economic empowerment, particularly for women in rural areas. This research contributes to the broader discourse on gender equality and rural development by providing a model that can be replicated in similar contexts